A COMPARATIVE STUDY OF PHRASEOLOGICAL UNITS RELATED TO PROFESSIONS IN ENGLISH AND UZBEK LANGUAGES - Akhmedova Zulfiya Guseynovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. Phraseological units play an important role in reflecting the cultural, social and professional realities of the linguistic community. This article examines phraseological units related to the profession in English and Uzbek, analyzes their structure, semantics, cultural connotations and usage. This study highlights both common features and differences due to linguistic and socio-cultural factors.